POLITIK, KERUDUNG, DAN FILM MASA ORDE BARU: GAMBARAN PERUBAHAN KERUDUNG DALAM FILM ISLAMI TAHUN 1977-1991 - Sumiati, Wina (Metahumaniora, 2025)
Abstract The use of the veil for Indonesian Muslim women was not very popular until the end of the 20th century. Apart from Islamic da'wah that has not been progressive, the New Order government's policy of restricting its use, especially in public schools through Decree No. 052 of 1982 is also one of the reasons. This ban was actually the beginning of the revival of Islam in the New Order era which had an impact on increasing awareness of wearing the veil in Indonesia. One way to see how changes in the use of the veil are reflected in society is through Islamic films produced during the New Order era. This article aims to analyze the representation of the use of the veil in three Islamic films—Al-Kautsar (1977), Titian Serambut Dibelah Tujuh (1982), and Nada and Da'wah (1991)—to understand the changes in the veiling style of Indonesian Muslim women during this period. Through film analysis, this article shows how the veil serves as a symbol of religion and identity, as well as how political and social influences affect that representation. The method used in this study is the historical method, including heuristic, source criticism, interpretation, historiography. The results of the study show that the change in the style of the hijab depicted in the film reflects the social, political, and increased consumption of Islam that occurred in Indonesia, from restrictions at the beginning of the New Order to the rise of Islamic consciousness in the late 1980s and 1990s.Keywords: Veil; New Order; Islamic films; Indonesia